A pilot exploration of the relationships between optimism, affect, and cardiovascular reactivity - Parra-Gaete, Cesar; Hermosa-Bosano, Carlos (Frontiers in Psychology, 2023)
Introduction Cardiovascular reactivity refers to changes in blood pressure and heart rate in response to internal or external stimuli. Previous research has shown that excessively high and low cardiovascular reactivity are associated with an increased risk of cardiac problems. Dispositional optimism has been associated with numerous health benefits, including better cardiovascular responses to stressors, and reduced mortality risk. Conversely, pessimism has been associated with negative health outcomes and worse cardiovascular reactivity to stress. Mood, comprising positive and negative affect, can significantly impact psychological adjustment and physical health. Therefore, it is important to consider mood as a potential confounding variable in the link between optimism and cardiovascular reactivity. The study hypothesized that optimism and pessimism would still influence cardiovascular reactivity even when mood variables were controlled for. Methods A within-subjects correlational design with 107 young adult participants was used. Sociodemographic and clinical questionnaires were administered to collect information on participants’ characteristics. The Dispositional Optimism Scale (LOT-R) and the Positive and Negative Affect Scale (PANAS) were used to assess participants’ levels of optimism, pessimism, and mood. Measures of cardiovascular reactivity, including systolic blood pressure (SBP), diastolic blood pressure (DBP), and heart rate (HR), were taken during a stressor task (PASAT). Results There is a moderate positive correlation between dispositional optimism and positive affect, while pessimism demonstrated a moderate positive association with negative affect. Linear regression analyses were conducted, controlling baseline reactivity variables, gender, and body mass index. The results showed that pessimism had a significant negative effect on SBP reactivity, suggesting that higher levels of pessimism decreased SBP response. Optimism had a significant positive effect on DBP reactivity, while pessimism had a significant negative effect. Discussion Overall, these results suggest that dispositional optimism and pessimism are related to cardiovascular reactivity, even after controlling for positive and negative affect. Pessimism was associated with lower SBP reactivity, while both optimism and pessimism influenced DBP reactivity. These findings are consistent with previous research indicating that optimism enables more effective stress management during challenging events, whereas pessimism can serve as a risk factor, heightening the likelihood of experiencing future cardiac issued caused by blunted cardiovascular reactivity.